165 Breast and cervical cancer screening utilisation among insured female employees at a large US company. (11th October 2013) - Starks, S E; Kreckmann,; Le,; Symons,
Abstract : Objectives: Female employees enrolled in a company-sponsored health insurance plan are eligible to receive preventive care benefits. We examined the utilisation of recommended screening tests for breast and cervical cancer among female employees of a large U. S. company. Methods: Using health insurance claims data, we identified female employees who were continuously enrolled from 2009 through 2011. The prevalence of biennial screening mammography among employees aged 40 to 64 years and the prevalence of Pap tests in the past three years among employees aged 21 to 64 years were calculated for groups defined by demographic and work characteristics. Results: Among 3, 972 female employees aged 40 to 64 years, 62% had at least one screening mammography in 2010 or 2011. Screening mammography utilisation did not differ substantially by race, marital status, pay-type or work location. Screening mammography utilisation was higher among employees aged 50 to 64 years (65%) compared to those aged 40 to 49 years (57%) and was higher among employees with day work schedules (64%) compared to those with rotating work schedules (51%). Among 4, 972 female employees aged 21 to 64 years, 74% had at least one Pap test within the past three years. Pap test utilisation was higher among employees aged 21 to 39 years (84%) compared to employees aged 40 to 49 years (76%) and 50 to 64 years (70%). Pap test utilisation was higher among employees with day work schedules (75%) compared to those with rotating work schedules (62%). Conclusion: More than one-half of female employees utilised recommended breast and cervical cancer screening tests; however, in the US population, the prevalence of screening mammography and Pap tests was 72% and 83%, respectively. Breast and cervical cancer screening for this insured employee cohort was slightly lower relative to the general US female population.